Digital Teaching Materials for Poetry Texts Oriented Towards the Pancasila Student Profile in SMA/SMK - Lubis, Rita Yosephine; Gloriani, Yusida; Mascita, Dede Endang (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to develop poetry text teaching materials that are presented digitally, are attractive, improve the character profile of Pancasila students, and are easy to use by teachers or students in learning Indonesian, especially poetry text materials for class X SMA/SMK students. Based on the research objectives, the output of this research is to produce digital teaching materials for poetry texts oriented towards Pancasila student profiles that are feasible and can be implemented in learning. The method used in this research is the development research method, which refers to the steps of the development model developed by Branch, namely, ADDIE. Development design is grouped into five procedures: analysis, Design, development, implementation, and evaluatione. Data collection used interview guidelines, observations, questionnaires for material experts, questionnaires for material experts, questionnaires for media experts, assessments from Indonesian language teachers, and material assessment instruments. The research results showed that the design of digital teaching materials for poetry texts based on expert validation obtained an average percentage of results of 81% with a very feasible category. The results of the implementation of 60 students with pre-test and post-test treatment show differences in average learning outcomes, so it can be concluded that the use of digital poetry text teaching materials oriented towards Pancasila student profiles can increase students' absorption in learning.